The Effects of Vitamin D Supplementation on Glucose Metabolism and Lipid Profiles in Patients with Gestational Diabetes: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Akbari, Maryam; Mosazadeh, Mahmood; Lankarani, Kamran B.; Tabrizi, Reza; Samimi, Mansooreh; Karamali, Maryam; Jamilian, Mehri; Kolahdooz, Fariba; Asemi, Zatollah (Hormone and Metabolic Research, 2017)
This systematic review and meta-analysis of randomized controlled trials (RCTs) was conducted to summarize the effect of vitamin D supplementation on glucose homeostasis parameters and lipid profiles in gestational diabetes (GDM) patients. We conducted an electronic systematic search of MEDLINE, and 4 other research databases from inception to August 2016, in addition to performing hand searches and consulting with experts in the field. The index of heterogeneity between studies was determined using Cochran (Q) and I-squared tests. Given the existing heterogeneity between studies, a fix or random effect model was performed to estimate the standardized mean difference (SMD) for each variable by using inverse variance method and Cohen statistics. Six randomized clinical trials (187 subjects and 184 controls) were included. The results showed that vitamin D supplementation significantly reduced the homeostasis model assessment of insulin resistance (HOMA-IR) [SMD −0.66; 95% confidence interval (CI), −1.14 to −0.18], homeostatic model assessment-B cell function (HOMA-B) (SMD −0.52; 95% CI, −0.79 to −0.25), LDL-cholesterol levels (SMD −0.33; 95% CI, −0.58 to −0.07), and significantly increased quantitative insulin sensitivity check index (QUICKI) (SMD 0.73; 95% CI, 0.26 to 1.20). We found no beneficial effect of vitamin D supplementation on fasting plasma glucose (FPG), insulin, HbA1c, total-, HDL-cholesterol, and triglycerides concentrations. In conclusion, this meta-analysis demonstrated that vitamin D supplementation may lead to an improvement in HOMA-IR, QUICKI, and LDL-cholesterol levels, but did not affect FPG, insulin, HbA1c, triglycerides, total- and HDL-cholesterol levels; however, vitamin D supplementation increased HOMA-B.
Keywords: vitamin D; glucose homeostasis; lipid profiles; meta-analysis